The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fneur.2018.00674
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Add-On Ultramicronized N-Palmitol Ethanol Amide in Patients Suffering of Migraine With Aura: A Pilot Study

Abstract: Background: Palmitoyl ethanol amide (PEA) is an endogenously produced substance showing anti-nociceptive effect through both receptor and non-receptor mediated effects at the level of different cellular and tissue sites. This study showed the results of a single blind study that was conducted to evaluate both the safety and the efficacy of ultramicronized PEA (umPEA; 1,200 mg/day) for up 90 days in patients suffering of Migraine with Aura (MA) treated with NSAIDs.Methods: A total of 20 patients, 8 male (33–56-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…In line with the study of Chirchiglia et al, our pilot study showed that umPEA at low doses (600 mg/kg/day) for short period (three months) is effective in reducing migraine attacks frequency and intensity in pediatric patients [17]. Our study also confirms the safety of treatment with umPEA.…”
Section: Pea In Migraine Prophylactic Treatmentsupporting
confidence: 91%
See 3 more Smart Citations
“…In line with the study of Chirchiglia et al, our pilot study showed that umPEA at low doses (600 mg/kg/day) for short period (three months) is effective in reducing migraine attacks frequency and intensity in pediatric patients [17]. Our study also confirms the safety of treatment with umPEA.…”
Section: Pea In Migraine Prophylactic Treatmentsupporting
confidence: 91%
“…To date, only one study has been conducted to evaluate the role of PEA in migraine management in adults [17]. e authors demonstrated that umPEA administration to patients with MA (1,200 mg/day for up 90 days) treated with common NSAIDs induced a significant pain relief irrespective to age or gender.…”
Section: Pea In Migraine Prophylactic Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrariwise, Andresen and colleagues reported that um-PEA did not alleviate pain in patients with spinal cord injuryinduced neuropathic pain, compared to placebotreated patients [126]. The efficacy of PEA in clinical trials and meta-analysis is however reviewed [127,128]. The actions of PEA on the neuroinflammation processes urderlying chronic pain are summarized in Figure 1.…”
Section: The Effect Of Um-pea On Chronic Painmentioning
confidence: 99%